2011
DOI: 10.1186/1472-6963-11-90
|View full text |Cite
|
Sign up to set email alerts
|

A snapshot of the organization and provision of primary care in Turkey

Abstract: BackgroundThis WHO study aimed to support Turkey in its efforts to strengthen the primary care (PC) system by implementing the WHO Primary Care Evaluation Tool (PCET). This article provides an overview of the organization and provision of primary care in Turkey.MethodsThe WHO Primary Care Evaluation Tool was implemented in two provinces (Bolu and Eskişehir) in Turkey in 2007/08. The Tool consists of three parts: a national questionnaire concerning the organisation and financing of primary care; a questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
70
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(84 citation statements)
references
References 7 publications
8
70
0
6
Order By: Relevance
“…[8][9][10][11] Supported by a growing body of evidence since Starfield's study in 1994, 12 decision makers increasingly use the strengthening of primary care in their strategy to cope with these challenges. 13,14 This study has built on previous studies that have evaluated primary care in individual countries, 15,16 or made international comparisons of a limited set of functions. 17,18 A major challenge in international comparative studies in primary care is to develop a suitable definition of primary care that can capture the variety in prevailing organisation and service-delivery models.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Supported by a growing body of evidence since Starfield's study in 1994, 12 decision makers increasingly use the strengthening of primary care in their strategy to cope with these challenges. 13,14 This study has built on previous studies that have evaluated primary care in individual countries, 15,16 or made international comparisons of a limited set of functions. 17,18 A major challenge in international comparative studies in primary care is to develop a suitable definition of primary care that can capture the variety in prevailing organisation and service-delivery models.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Bir baflka kaynakta ülkemizde bir aile hekimi ve aile sa¤l›¤› eleman›n-dan oluflan AHB'nin hizmet verdi¤i nüfus büyüklü¤ünün ortalama 3.700 kifli oldu¤u, bunun Avrupa ülkelerindeki say›lar›n (orne¤in; Hollanda'da 2.322, Polonya'da 1.539, ‹talya'da 1.094) çok üzerinde oldu¤u belirtilmektedir. [9] Nüfus bafl›na düflen aile hekimi say›s›nda ülkeler aras›nda bariz farklar vard›r. 2002 y›l› verilerine göre 1.000 kifli bafl›na düflen aile hekimi say›s› en fazla olan ülkeler s›ras›yla 2.1 aile hekimi ile Belçika, 1.7 ile Finlandiya, 1.6 ile Fransa ve 1.4 ile Avusturya olmufltur.…”
Section: Tart›flmaunclassified
“…Although such durations were found to be prolonged for some countries, it is also reported that such a prolongation alone is not sufficient to induce health promotion and behavioral modifications [2,3,4]. With its rapidly increasing prevalence and intricate nature, obesity emerges as a chronic health problem, which may not be solved through conventional approaches due to time constraints.…”
Section: Introductionmentioning
confidence: 99%
“…Primary care, where chronic diseases show higher prevalence, is deemed as a significant resource to solve the problem of obesity because of the longitudinal sustainability in physician-patient relationship. However, daily patient log of primary care is quite high in our country, and there are not any programs commonly used for obesity [2]. Since it is a new practice concept for our primary care, it is difficult to predict the feasibility of group medical visit.…”
Section: Introductionmentioning
confidence: 99%